WHAT ARE THE CULTURAL IMPACTS FROM THE DEVELOPMENT OF TOURISM VILLAGE? - Priyanto, Sabda Elisa; Pirastyo, Swastono Putro (THE Journal : Tourism and Hospitality Essentials Journal, 2019)
This study focused on the tourism impact on the culture of Kebonagung tourism village, Imogiri, Bantul, Yogyakarta. The method used in this study was qualitative descriptive and using the case study approach. Data were collected through observation, interview and literature review. Cultural component data were presented descriptively, and they explained about how tourism brought effects to them. The transformational condition of the culture itself contained many aspects such as; religion, socio-cultural, livelihood, technology growth, language and art. The goal of this study was to find tourism impacts on Kebonagung Society. In religion, the impact towards the society was they could positively accept the diversity of religion. However, the local religion system also became the biggest challenge to develop tourism. Tourism also gave a positive impact to the society organizational system. It made the society more open minded. When tourism brought foreign culture inside, it also threated the local society organizational system. Other impact was the livelihood of the local society can be widely known, but it also potentially faded the originality of the culture itself by the tourist. In the language aspect, tourism helped Javanese Language and Javanese Script to be widely used especially in tourism activity. From the negative side, local language also had to compete with foreign language. The effect of tourism development in the field of art was that it brought art closer to society, but foreign art and culture can also rub the local art and culture.Â